Neural evidence for lexical parafoveal processing - Yali Pan (Nature Portfolio, 2021)
When reading, we extract information about upcoming words before we saccade to them. Here the authors provide insights on the neural mechanisms supporting this previewing process using MEG data, and show an association between previewing effects and reading speed.